Whole-Exome Sequencing Identifies Novel SCN1A and CACNB4 Genes Mutations in the Cohort of Saudi Patients With Epilepsy - Naseer, Muhammad Imran; Abdulkareem, Angham Abdulrhman; Rasool, Mahmood; Algahtani, Hussein; Muthaffar, Osama Yousef; Pushparaj, Peter Natesan (Frontiers in Pediatrics, 2022)
Epilepsy is a neurological disorder described as recurrent seizures mild to severe convulsions along with conscious loss. There are many different genetic anomalies or non-genetic conditions that affect a brain and cause epilepsy. The exact cause of epilepsy is unknown so far. In this study whole exome sequencing (WES) showed a family having novel missense variant c.1603C>T, p. Arg535Cys in exon 10 of Sodium Voltage-Gated Channel Alpha Subunit 1 (SCN1A) gene and c.1212A>G p.Val404Ile in 15 unrelated patients from the cohort of 25 epileptic sporadic patients. We have also identified a mutation in Calcium Voltage-Gated Channel Auxiliary Subunit Beta 4 (CACNB4) gene and the sequencing results showed one base pair insertion of “G” nucleotide in exon 3 where c.78_79insG, p.Asp27Glyfs*26 in three different patients. The insertion change the amino acid sequence leading to a frameshift mutation. Here, we have described, for the first time, three novel mutations associated with epilepsy in the Saudi population. The study not only help us to identify exact cause of genetic variations causing epilepsy whereas, it would eventually enable us to establish a database provide a foundation to understanding the critical genomic regions to control the epilepsy in Saudi patients.